2018
DOI: 10.1111/apv.12178
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phones, gender‐based violence, and distrust in state services: Case studies from Solomon Islands and Papua New Guinea

Abstract: This paper examines the potential benefits and pitfalls of mobile phones for accessing social services, particularly in response to gender‐based violence, in Solomon Islands and Papua New Guinea. Drawing on 13 months of ethnographic field research, I show how mobile phones increase rather than decrease perceived distances between social service providers and those they intend to serve. Mobile phones exaggerate the visibility of the shortcomings of the Solomon Islands and Papua New Guinea states and solidify an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…Nonetheless, each phone that we encountered had a clear owner who had control over its usage as well as the numbers and multimedia files stored on the particular phone, as well as both its SIM and MicroSD cards. Despite significant controversies and conflicts surrounding women’s and men’s respective usages of mobile phones (Hobbis, 2017a, 2018b), we did not notice significant gendered divisions in mobile phone ownership. Both men and women individually owned them, often primarily depending on who had been able to afford, or been gifted, one.…”
Section: Introductioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Nonetheless, each phone that we encountered had a clear owner who had control over its usage as well as the numbers and multimedia files stored on the particular phone, as well as both its SIM and MicroSD cards. Despite significant controversies and conflicts surrounding women’s and men’s respective usages of mobile phones (Hobbis, 2017a, 2018b), we did not notice significant gendered divisions in mobile phone ownership. Both men and women individually owned them, often primarily depending on who had been able to afford, or been gifted, one.…”
Section: Introductioncontrasting
confidence: 71%
“…Moral controversies are also a threat to the survival of mobile phones themselves. Jealous partners regularly smash them because they suspect mobile phone owners of having used their phones, for instance, to coordinate extramarital affairs (see also Hobbis, 2018b; Mantz, 2018). Additional problems arise from the tropical and maritime environment to which mobile phones are exposed.…”
Section: Introductionmentioning
confidence: 99%
“…When we asked if mobile phones could not ameliorate some of these concerns, by allowing engagement with state representatives from the village or by providing advice on village affairs from town, our respondents generally answered with a disappointed ‘no.’ Calling state services was seen by many as more unreliable than going in person (Hobbis 2018). Respondents who tried this option were told to ‘call back tomorrow’ or, most of the time, they did not reach anyone in the first place.…”
Section: Urban Village Leadersmentioning
confidence: 99%
“…Research in Papua New Guinea and the Solomon Islands has identified that community education may be required to support and encourage the use of mobile phones for clinical consultations, and training is essential for health care providers to optimize consultation outcomes. 10 Wherever possible clients should be counselled on the benefits of LARC, as part of a wider range of contraceptive methods, as these methods will provide long-term protection and reduce the need for clinic visits. IPPF advises informing clients about the following: keeping subdermal implants for 5 years regardless of their type, using levonorgestrel-releasing intrauterine systems (LNG-IUS 52 mg) for 7 years, and copper intrauterine devices (Cu-IUD) for up to 12 years during the pandemic if access to a clinic for removal or replacement is not possible.…”
Section: Opportunities For Actionmentioning
confidence: 99%